Public expenditure and performance of the agricultural sector: evidence from Sri Lanka - Vickneswaran, Anojan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study investigates the influence of agricultural public expenditure on the performance of Sri Lanka's agriculture sector. Utilizing data sourced from the annual reports of the Ministry of Finance spanning 2011 to 2022, the findings reveal a significant and positive correlation between the recurrent expenditure of the Department of Agriculture (DoA) and the gross domestic production of the agriculture sector (p < 0.01). However, no statistical evidence supports a significant relationship between the Ministry of Agriculture's (MoA) capital expenditure and DoA and the performance of the agriculture sector. These results underscore the pivotal role of public recurrent agricultural expenditure in bolstering the agriculture sector's performance. Particularly noteworthy is the significant impact of DoA's recurrent expenditure on sectoral performance. The study advocates for increased budget allocation towards recurrent expenditure within the agriculture sector, especially emphasizing the importance of augmenting the DoA's recurrent expenditure to ensure enhanced performance and sustainability. Ultimately, the study underscores the critical importance of effective and efficient management of public funds in driving the agriculture sector's performance.